The Role of “Slow Territories” in the Development of Sustainable Tourism - Pavione, Enrica; Pezzetti, Roberta; Gazzola, Patrizia (European Scientific Journal, ESJ, 2017)
The paper intends to propose an analysis of the so called “slow territories”, sometimes little known contexts that present a significant set of both tangible and intangible resources often characterized by levels of excellence, by investigating in particular their role in the development of sustainable tourism. In recent years, the international tourism market highlights important chances, both as regard the demand and supply sides, and an increasing attention and sensitivity to sustainability understood in its social, environmental and economic dimension The emergence of a substantial segment of demand more aware and attentive to the sustainable dimension of the holiday is connected to the growth of the cultural level of tourists: in this framework the increasing awareness of environmental issues, the respect and desire to learn about the traditions of local cultures are becoming key criteria in the choice of tourist destinations. These trends have led to the emergence of a new type of tourist, who aims to live a territory and to interact with the local community, in a relationship of mutual exchange, which translate into a new experiential dimension of the holiday. In this perspective the “slow territories” represent not only a model of local development, but also a growth trajectory that combines economic growth, social cohesion, entrepreneurial innovation and environmental protection, with a view to sustainability.